Impact of Sediment Formed in Biogas Production on Productivity of Crops and Ecologic Character of Production of Onion for Chives (Agricultural Engineering, 2018)
The solid fraction, according to many researches, is an effective organic fertilizer, the activity of which is at the level of mineral fertilizers and even exceeds their effectiveness, while the use of the liquid fraction does not always give positive results. In the article the optimal concentration of the liquid fraction in water solution for fertilization during cultivation of onion for chives in soil was determined. Sediment from biogas production was obtained at the thermophilic fermentation (50ºC) of cattle manure in the laboratory institution which operated at the periodical regime of loading. Fermentation lasted 25 days. Seven variants of plant feeding were assessed: clean water (control), mineral fertilizers (solution of ammonium nitrate in water in the concentration of 1:25), unsolved liquid biofuel fraction and mixture of liquid fraction from the postferment with water in concentrations of 1:10, 1:50, 1:100, 1:500. It was determined that the highest efficiency was observed in case of fertilization of plants with the mixture of liquid fraction from postferment with concentration of 1:500. Along with the increase of liquid fraction concentration and fertilization of plants with water solution of mineral fertilizers, onion productivity dropped slightly. Fertilization of plants with the liquid fraction from postferment resulted in fractional dying of plants and reduction of efficiency. The crop control of nitrogen content proved that in case of every day watering of onion with clean water and mixture of liquid fraction with water concentration of 1:100-1:500 did not exceed the maximum admissible concentration which is 800 mg·kg−1. Thus, in case of onion cultivation for chives, taking into consideration the crop growth and low nitrogen content, it is recommended to use the mixture of liquid fraction with water of 1:500 concentration.